The impact of higher fees on psychology students' reasons for attending university. Issue 3 (4th May 2017) - Kaye, Linda K; Bates, Elizabeth A
Abstract: The introduction of the new UK tuition fees resulted in concerns about the impact on higher education (HE) uptake, and raised questions regarding students' motivations for attending university. The current study explored first-year undergraduate psychology students' ( N  = 56) reasons for attending HE through a series of focus groups. These were undertaken both before ( n  = 21) and after ( n  = 35) the rise in fees, providing a pre–post comparison of potential changes. Results from the pre-fee rise sample showed that general reasons for attending HE reflected wider, contextual factors, drawing on socio-cultural influences. However, the post-fee rise data suggested that HE uptake was largely motivated more by career opportunities associated with degree-level education. Similarly, reasons for choosing psychology-based courses was related to vocational interest, suggesting strategic decision-making processes of students embarking on HE. The findings present new evidence of the role of financial investment in HE on general and course-specific motivation. Implications of the findings are discussed, with particular reference to the development of relevant employability initiatives within HE curricula.